Assessing Employability: Tracing BA Sociology Graduates from MSU-Iligan Institute of Technology, Philippines - Embornas, Amabelle; Ponce, Sulpecia (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study evaluated the employability of Bachelor of Arts in Sociology graduates from MSU-Iligan Institute of Technology, focusing on their demographic profile and employment characteristics. Using the Input, Process, Output (IPO) model and a sample of 153 graduates from 2016 to 2021, the research found that the majority of participants were female, with 78% employed primarily in government, private sectors, and NGOs, earning between 10,000 and 14,999 pesos monthly. Most graduates secured their first job within a year and found their degree relevant to their roles. Key skills such as work ethics, teamwork, verbal communication, and interpersonal skills were highlighted as valuable in the workplace. The study also noted high satisfaction with the program’s faculty,curriculum, facilities, and library resources, affirming the curriculum’s relevance and competitiveness in the job market. Recommendations included enhancing internships, immersive activities, and faculty-student relations. However, the findings may not fully capture current job market conditions. Future research could investigate graduates’ job satisfaction, the perceived relevance of their education, and their lived experiences in the workforce.